MIDWIFERY CARE FOR NORMAL NEWBORN NY.N AT HJ. HENDRAYATNI CLINIC, PEMATANGSIANTAR CITY YEAR 2020 - Mareny, Riada; Alexander, Alexander; Wardati, Jumadiah; Sihombing, Eka; Nurmala, Nurmala (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
Background: Normal newborns (neonates) are born weighing between 2500-4000 grams, full months, born crying immediately, and no congenital abnormalities (congenital defects). Literature Review: Physiological changes in newborns, prevention of infection, handling of newborns, prevention of heat loss, practice of bathing babies, how to breastfeed babies Purpose: This goal is to provide midwifery care for newborns. Methods: The data collection method consists of primary data, namely physical examination (inspection, auscultation, percussion), interviews and observations (vital singn and general condition) Results: Mrs. N already knows about the explanation of newborns, Mrs. N already knows the results of the examination baby, Mrs. N already knows about newborn care. Conclusion: As long as the care given to Baby Mrs. N can be carried out properly,